Doses for X‐ray and electron diffraction: New features in RADDOSE‐3D including intensity decay models - Dickerson, JL; McCubbin, PTN; Brooks‐Bartlett, JC; Garman, EF (Wiley, 2024)
New features in the dose estimation program RADDOSE‐3D are summarised. They include the facility to enter a diffraction intensity decay model which modifies the “Diffraction Weighted Dose” output from a “Fluence Weighted Dose” to a “Diffraction‐Decay Weighted Dose”, a description of RADDOSE‐ED for use in electron diffraction experiments, where dose is historically quoted in electrons/Å2 rather than in gray (Gy), and finally the development of a RADDOSE‐3D GUI, enabling easy access to all the options available in the program.